Postoperative respiratory management in living donor lobar lung transplantation. (11th June 2013) - Chen, Fengshi; Chin, Kazuo; Sato, Masaaki; Aoyama, Akihiro; Murase, Kimihiko; Azuma, Masanori; Bando, Toru; Date, Hiroshi
Abstract Background We evaluated postoperative respiratory management of living donor lobar lung transplantation (LDLLT). Methods Perioperative variables were reviewed in 21 patients who underwent LDLLT at our institution. Recipients were kept intubated for at least two d after LDLLT to maintain optimal expansion of the implanted lobes. Subsequently, if weaning from artificial ventilation could be tolerated, extubation was considered with the assistance of non‐invasive ventilation (NIV). If this could not be tolerated, early tracheostomy was considered. Results All 21 recipients were weaned from artificial ventilation. Twelve patients underwent tracheotomy 4.4 ± 1.8 d after LDLLT and were weaned from artificial ventilation 24.3 ± 17.0 d after LDLLT. Eleven patients were extubated 3.6 ± 1.7 d after LDLLT with NIV, but two of them were reintubated, and finally weaned from artificial ventilation via tracheostomy. Excluding these two patients, NIV was required for 3.8 ± 3.9 d after extubation. The early postoperative course was significantly eventful in patients with tracheostomies, and artificial ventilation, ventilatory support, and intensive care unit stays were longer. Twenty patients (95%) showed survival at 24.4 ± 13.4 months of follow‐up. Conclusions Postoperative respiratory management with NIV and early tracheostomy were useful after LDLLT.